Analisis Tingkat Pemahaman Perangkat Desa Terhadap Asas Pelayanan Publik Dalam Rangka Mewujudkan Pelayanan Publik Yang Prima - Syifaa Afelyna Suryoputri; Sri Nurhari Susanto (Administrative Law and Governance Journal, 2022)
Abstract: Village officials have an important role in improving the quality of public services, so understanding village officials on the principles of public service is a must. However, the Human Resources (HR) of the Sidomulyo Village apparatus have so far been inadequate and seem sober. Making the principle of public service the basis for public service must be followed by an understanding of the village officials towards these principles. The approach method in this research is Juridical Empirical, using primary and secondary data. The findings in this study are, first, the level of understanding of Sidomulyo Village Officials regarding the principles of public service delivery is at the middle level, this can be seen by fulfilling 2 of the 3 indicators of understanding, namely translating and interpreting. Second, the level of understanding of Sidomulyo Village Officials regarding the principles of public service delivery greatly influences the realization of excellent service. Third, the embodiment of excellent service can be seen from the fulfillment of the A6 competency in the excellent service of an organization. The results of this study suggest: (1) increasing the understanding of Village Officials on the principles of public service delivery, (2) learning the basics of excellent service and implementing it, (3) increasing the role of the community in administering public services and (4) increasing employee competence. Keywords: Design Tools, Principles, Public Service, Excellent Service. Abstrak: Perangkat desa memiliki peranan penting dalam peningkatan kualitas pelayanan publik, sehingga pemahaman perangkat desa terhadap asas pelayanan publik merupakan suatu keharusan. Namun, Sumber Daya Manusia (SDM) Perangkat Desa Sidomulyo selama ini masih kurang memadai dan terkesan seadanya. Menjadikan asas pelayanan publik sebagai dasar pelayanan publik harus diikuti dengan pemahaman perangkat desa terhadap asas-asas tersebut. Metode pendekatan dalam penelitian ialah Yuridis Empiris, dengan menggunakan data primer dan sekunder. Temuan dalam penelitian ini berupa, pertama tingkat pemahaman Perangkat Desa Sidomulyo terhadap asas penyelenggaraan pelayanan publik berada pada tingkat madia, hal tersebut dapat diketahui dengan terpenuhinya 2 dari 3 indikator pemahaman yakni menerjemahkan dan menafsirkan. Kedua, tingkat pemahaman Perangkat Desa Sidomulyo terhadap asas penyelenggaraan pelayanan publik sangat berpengaruh terhadap perwujudan pelayanan prima. Ketiga, perwujudan pelayanan prima dapat dilihat dari terpenuhinya kompetensi A6 dalam pelayanan prima sebuah organisasi. Hasil dari penelitian ini menyarankan: (1) meningkatkan pemahaman Perangkat Desa terhadap asas penyelenggaraan pelayanan publik, (2) mempelajari dasar pelayanan prima dan mengimplementasikannya, (3) meningkatkan peranan masyarakat dalam penyelenggaraan pelayanan publik dan (4) meningkatkan kompetensi pegawai. Kata Kunci: Perangkat Des, Asas, Pelayanan Publik, Pelayanan Prima.